INFLUENCE ON PROOXIDANT-ANTIOXIDANT HOMEOSTASIS OF SPERM PRODUCTION IN BOARS DURING HEAT STRESS - Pavlova, I. V. (Scientific Progress & Innovations, 2022)
In current conditions, in the conditions sharp change of climate, the main factor of growth productivity on revealing of adaptive properties an organism under the influence of thermal stresses. The aim of the study was to determine on prooxidant- antioxidant homeostasis of sperm of boars of different breeds during heat stress. The experiment used adult boars of two breeds of Poltava meat (PM) and red and white meat (RWB), analogues in age, live weight and quality of sperm produced, during heat stress. It is established that in the period of thermal stress in the semen of boars prooxidant-antioxidant homeostasis is shifted towards the acceleration of peroxidation: stable growth in the semen of PM rocks of the number of dienes . conjugates and TBA-active complexes; RWB breed had a negative effect up to 30 days of the experiment with the subsequent development of an adaptive response. Such changes were accompanied by a decrease in superoxide dismutase activity in PM (p <0.01) and the content of reduced glutathione and ascorbic acid with a parallel increase in catalase activity. The unequal influence of heat stress on the formation of prooxidant- antioxidant homeostasis in the semen of boars of different breeds was revealed. It was found that inactivation (SOD activity) of reactive oxygen species has significantly higher functional activity (p<0.01) in representatives of the RWB compared to PM. The level of saturation of this tissue with reduced glutathione and DAC was higher in animals of PM breed. It was found that in the period of the experiment with increasing intensity of oxidative processes, there was a manifestation of adaptation to the adverse effects of ultra-high temperatures on the 70th day of the experiment. Thus, compared with RWB breeds, PM animals had a more effective effect of feed additives, which was manifested in the rapid recovery of glutathione, ascorbic acid, as well as in the reduction of diene conjugates and TBA-active complexes, which indicates an earlier activation of the adaptive processes of the organism of the second genotype under heat stress.